Anaerobic power in road cyclists is improved after 10 weeks of whole-body vibration training - Oosthuyse, T.; Viedge, A.; McVeigh, J.; Avidon, I. (The Journal of Strength and Conditioning Research, 2013)
Whole-body vibration (WBV) training has previously improved muscle power in various athletic groups requiring explosive muscle contractions. To evaluate the benefit of including WBV as a training adjunct for improving aerobic and anaerobic cycling performance, road cyclists (n = 9) performed 3 weekly, 10-minute sessions of intermittent WBV on synchronous vertical plates (30 Hz) while standing in a static posture. A control group of cyclists (n = 8) received no WBV training. Before and after the 10-week intervention period, lean body mass (LBM), cycling aerobic peak power (Wmax), 4 mM lactate concentration (OBLA), VO2peak, and Wingate anaerobic peak and mean power output were determined. The WBV group successfully completed all WBV sessions but reported a significant 30% decrease in the weekly cycling training time (pre: 9.4 ± 3.3 h/wk; post: 6.7 ± 3.7 h/wk; p = 0.01) that resulted in a 6% decrease in VO2peak and a 4% decrease in OBLA. The control group reported a nonsignificant 6% decrease in cycling training volume (pre: 9.5 ± 3.6 h·wk-1; 8.6 ± 2.9 h/wk; p = 0.13), and all measured variables were maintained. Despite the evidence of detraining in the WBV group, Wmax was maintained (pre: 258 ± 53 W; post: 254 ± 57 W; p = 0.43). Furthermore, Wingate peak power increased by 6% (668 ± 189 to 708 ± 220 W; p = 0.055), and Wingate mean power increased by 2% (553 ± 157 to 565 ± 157 W; p = 0.006) in the WBV group from preintervention to postintervention, respectively, without any change to LBM. The WBV training is an attractive training supplement for improving anaerobic power without increasing muscle mass in road cyclists.